Analytical Approach for Data Encryption Standard Algorithm - Al-hazaimeh, Obaida M.; Al-Shannaq , Moyawiah A.; Bawaneh , Mohammed J.; Nahar , Khalid M.O. (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Although it was first developed and studied in the late 1970s and early 1977s, the Data Encryption Standard (DES) algorithm has grown in popularity. There are two causes for this occurrence. First, the DES algorithm's complex mathematical structure allows it to serve as the theoretical foundation for a wide variety of applications. Second, the encryption technique works quite well in practice for a variety of applications when implemented correctly. In this paper, we undertake a thorough and practical review of the theoretical aspects of this sort of encryption algorithm and demonstrate how they have been implemented by executing multiple encryption configurations.